2013
DOI: 10.1073/pnas.1218714110
|View full text |Cite
|
Sign up to set email alerts
|

Chicken hemogen homolog is involved in the chicken-specific sex-determining mechanism

Abstract: Using a comprehensive transcriptome analysis, a Z chromosomelinked chicken homolog of hemogen (cHEMGN) was identified and shown to be specifically involved in testis differentiation in early chicken embryos. Hemogen [Hemgn in mice, EDAG (erythroid differentiation-associated gene protein) in humans] was recently characterized as a hematopoietic tissue-specific gene encoding a transcription factor that regulates the proliferation and differentiation of hematopoietic cells in mammals. In chicken, cHEMGN was expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 32 publications
6
53
0
1
Order By: Relevance
“…DMRT1 has been suggested to activate the testicular marker SOX9 indirectly because of the time lag between DMRT1 and SOX9 expression (day 4.5 and day 6.5 of incubation, respectively), and the chicken homolog of hemogen (cHEMGN) was shown to link the expression of both [Nakata et al, 2013]. In line with this, we observed an exclusive expression of cHEMGN in male gonads.…”
Section: High Usual Suspects Ratiosupporting
confidence: 83%
“…DMRT1 has been suggested to activate the testicular marker SOX9 indirectly because of the time lag between DMRT1 and SOX9 expression (day 4.5 and day 6.5 of incubation, respectively), and the chicken homolog of hemogen (cHEMGN) was shown to link the expression of both [Nakata et al, 2013]. In line with this, we observed an exclusive expression of cHEMGN in male gonads.…”
Section: High Usual Suspects Ratiosupporting
confidence: 83%
“…DMRT1 is located on what is probably the most ancient evolutionary strata shared amongst all major lineages, supporting the notion that it is a universal testis determinant in birds [Chue and Smith, 2011;Zhou et al, 2014]. Recently, another Z-linked gene, HEMGN , has been implicated in testicular morphogenesis in the chicken [Nakata et al, 2013] ( fig. 1 A).…”
Section: Avian Sex Determination and Gonadal Sex Differentiationmentioning
confidence: 61%
“…This gene encodes a nuclear protein, Hemogen, which is involved in haematopoiesis in mammals (but not gonadal sex differentiation). It is expressed in male but not female embryonic chicken gonads, and forced overexpression in ZW females can induce upregulation of male marker genes, including DMRT1 [Nakata et al, 2013]. It is possible that HEMGN lies upstream of DMRT1 in chicken gonadal sex differentiation.…”
Section: Avian Sex Determination and Gonadal Sex Differentiationmentioning
confidence: 99%
“…In this context, it has recently been reported that the Z-chromosome gene hemogen is expressed at higher levels in the left and right medulla of male gonads than of female gonads between HH28 and HH35. Overexpression of this transcription factor in female embryos caused decreased FOXL2/ P450arom expression and increased SOX9 expression compared to controls and a degree of female to male gonad sex reversal, suggesting that this gene could also play a role in testis determination [Nakata et al, 2013].…”
Section: L:r Asymmetry and Sex (Gonadal) Determinationmentioning
confidence: 99%